Clara Schumann: Complete Songs Miriam Alexandra sop, Peter Gijsbertsen ten, Jozef De Beenhouwer pf Musikproduktion Dabringhaus und Grimm MDG9032114, 2019 (1 CD: 71 minutes) - Tan, Cheryl (Nineteenth-Century Music Review, 2024)
The tradition of celebrating composers at significant anniversaries has grown ubiquitous in the western musical world, having taken a strong foothold particularly since the twentieth century. In 2019, scholars and performers on both sides of the Atlantic convened in commemoration of the bicentenary of Clara Schumann. In England, Clara Schumann (née Wieck) and her World was held at the University of Oxford. In North America, Performing Clara Schumann: Keyboard Legacies and feminine Identities in the Long Romantic Tradition took place at Cornell University. That same year, two compact discs also were released by Musikproduktion Dabringhaus und Grimm (MDG) and Edelweiss Emission. The former, Clara Schumann: Complete Songs, encompasses her twenty-nine currently known Lieder while the latter, Clara Schumann Piano Works, surveys a sample of her piano music.
PUBLISHED
Keywords: HUMANITIES and RELIGION::Aesthetic subjects::Music; Performance Practice; Nineteenth-Century; Music History; Piano; Creative Arts Practice; Musicology/Music Theory; PERFORMANCE